The Influence of the Role of Parents on the Learning Achievement of Students of SDN Margorejo III Surabaya - Venasya Permata Zamrud (BASICA, 2024)
This study aims to examine the influence of parental roles on students' academic achievement and identify specific roles that contribute to academic success. Using a non-experimental quantitative approach with a survey method, this study ensures the validity of the data through normality tests (Shapiro-Wilk) and homogeneity tests (Bartlett). A simple linear regression analysis was used to measure the influence of variable X (parental role) on variable Y (student academic achievement). The results showed a correlation between parental roles and academic achievement, although the effect was not statistically significant. These findings are expected to provide more in-depth insights into the factors that affect students' academic success and serve as a basis for further research.